2021
DOI: 10.30564/mmpp.v2i4.2632
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Tax Avoidance: Evidence from Nigerian Quoted Food and Beverage Companies

Abstract: The study examined the effect of corporate governance on tax avoidance of quoted food and beverage companies in Nigeria. Specifically, the study seeks to determine the effect of CEO duality on effective tax rate of quoted foods and Beverage companies. Ex post facto research design was adopted. The population of this study covered twelve (12) Foods and Beverages quoted on the Nigerian Stock Exchange as at 2019. Purposive sampling technique was applied (Non-random sample) in selecting nine (9) companies during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Prior literature examining the relationship between CEO duality and TA documented mixed results. Consistent with the agency theory and recommendations of CG codes, there are studies that found a positive relationship between CEO duality and TA, indicating that the lack of separation between the two roles led to higher TA practices, which provided opportunities for rent-extraction by managers (Ezejiofor & Ezenwafor, 2021).…”
Section: Ceo Duality and Tax Avoidancementioning
confidence: 58%
“…Prior literature examining the relationship between CEO duality and TA documented mixed results. Consistent with the agency theory and recommendations of CG codes, there are studies that found a positive relationship between CEO duality and TA, indicating that the lack of separation between the two roles led to higher TA practices, which provided opportunities for rent-extraction by managers (Ezejiofor & Ezenwafor, 2021).…”
Section: Ceo Duality and Tax Avoidancementioning
confidence: 58%
“…Manajemen menginginkan keuntungan dengan mengakomodasikan kompensasi yang memadai untuk usaha yang dilakukan, sedangkan prinsipal lebih mengutamakan tingkat pengembalian atas investasi yang telah diberikan pada perusahaan, hal ini menimbulkan perbedaan tujuan yang menyebabkan konflik atas keuntungan pada hubungan agensi (Parinduri, Pratiwi, & Purwaningtyas, 2018). (Ezejifor & Ezenwafor, 2020). Tax Avodance pada penelitian ini diukur dengan rumus seperti berikut:…”
Section: Agency Theoryunclassified
“…One element that has been found to impair the financial success of food and beverage companies is weak corporate governance. Research has indicated that enhancing company governance, encompassing elements like board independence and composition, can improve returns on assets and financial performance [2], [3]. In order to offset the decline in sales in high-income countries, the food and beverage sectors have also been concentrating on prospects in low-and middle-income nations.…”
Section: Introductionmentioning
confidence: 99%